Future of Work: The Pivot to Outcomes and Quantum - Vijay, Chendil Nathan T (Digital Repository of Theses - SSBM Geneva, 2025)
Just like the world at large, the world of work shifts and changes over time. The future of work refers to an informed perspective on what businesses and other organizations need to know about how work could shift (given digitization and other trends), plus how workforces and workplaces can prepare for those changes, big and small. It’s the heyday of flex-work models, but the future of work is so much more, with opportunities ready to be tackled along the spectrum of workforce transformation. This study explores the future of work, focusing on factors influencing remote and offshore delivery, harmonized methodologies for delivery quality, employee development, and cloud environment management. The objective is to reveal how work systems and human capital might be best managed for an organisation to achieve change in the light of new technologies or organisational environments. Accelerated digitalization and technology advances fuel the need for skill transformations across large portions of today’s workforce. The extension of clouds to the edges benefits the expansion and functionality of more extended and efficient networks together with other technologies such as artificial intelligence, virtual reality, and quantum computing, among others are just a few of the emerging technologies dominating headlines. Quantum ERP and computing are important. This research work adopted a quantitative research approach using a survey of 168 respondents drawn across proficiency, age, and years of practice. Calculation of correlation coefficients, particularly Spearman’s correlation analysis, was done in a bid to compare the connections between the important variables with a view of identifying patterns. Some of the variables included working model flexibility, technology integration, labour diversity, quantum computing, and cloud computing administration. The study concludes that organizations must embrace technological advancements, prioritize employee development, and foster inclusive environments in technological transformation, diversity, and sustainability to remain competitive. Organisations must focus on Quantum literacy and Technology Education for Leaders, fairness in the Future of work and strategic focus on cloud adoption, harmonized methodologies to enhance operational efficiency and innovation, positioning businesses for sustainable growth in the evolving landscape of work.